2012
DOI: 10.11113/jt.v58.2543
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Metallic Earring on Antenna Performance and SAR at 2.4 & 5.8 GHz

Abstract: This paper presents an investigation on the effect of metallic items on the antenna performance and SAR at 2.4 GHz and 5.8 GHz frequencies. The simulations are performed by means of CST Microwave Studio. The patch dipole antenna is used as the radiating source while the metallic items are modeled as /4 and /2 straight pin-type earrings respectively. The results show that the presence of the head shifted the antenna resonant frequencies and modify the antenna radiation pattern at both investigated frequencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…At present, the interactions between the electromagnetic wave and human biological tissues have been widely investigated in [1][2][3][4][5]. Based on [6][7][8][9][10], the presence of additional metallic items could significantly enhance the total power absorbed by the human tissues. Besides, [6,11] reported that patients with implanted item potentially suffer from heating while undergo the MR procedures.…”
Section: 10 Introductionmentioning
confidence: 99%
“…At present, the interactions between the electromagnetic wave and human biological tissues have been widely investigated in [1][2][3][4][5]. Based on [6][7][8][9][10], the presence of additional metallic items could significantly enhance the total power absorbed by the human tissues. Besides, [6,11] reported that patients with implanted item potentially suffer from heating while undergo the MR procedures.…”
Section: 10 Introductionmentioning
confidence: 99%